SINTESIS DAN UJI TOKSISITAS SENYAWA KALKON ANALOG 2,5-DIMETOKSIBENZALDEHID - Hidayat, T.; Zamri, A. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Chalcones are a class of Î±,Ã-unsaturated carbonyl compounds that forms the central coreof various naturally occurring biologically active compounds. They exhibit tremendouspotential to act as a pharmacological agent. It has been reported that they were active asantioxidant, antifungal, antibacterial, antidepressant, anticancer, anti-inflammatory andother biological activities. The chalcone analogue of 2,5-dimetoxibenzaldehyde ((E)-3-(2,5-dimetoksifenil)-1-(4-hidroksifenil)prop-2-en-1-on) was synthesized and tested forits toxicity using Brine Shrimp Lethality Test (BSLT) method. The purity of compoundhas been tested using TLC, melting point test, analytical HPLC. It was thencharacterized using UV, IR, 1 H-NMR and MS spectroscopy. LC 50 value of toxiccompound is <200Î¼g/mL. Our result showed that (E)-3-(2,5-dimetoksifenil)-1-(4-hidroksifenil)prop-2-en-1-on compound was not potential as an anticancer since itsLC 50 was 1949 Î¼g/mL.